A violência impera nessa cidade: reflexões sobre o medo de assaltos em Fortaleza-CE - Costa, Fernanda Vieira Crisóstomo da (2018)
This thesis has as the object of analysis residents of the city of Fortaleza-CE who fear going through situations of robberies in the urban environment, seeking to perceive who these individuals are and how their sociabilities are altered through the sensation of fear and insecurity. In this sense, the focus of the research is to understand the relationship between fear and violence in situations of assault, trying to analyze how it interferes in the daily lives of those who inhabit the capital of Ceará. After analyzing the data collected, the study indicates that the expectation or the experience of having been in a situation of assault alter the relations of sociability, interfering in the way that people move on the streets, make them adopt individual security measures, start to observe the other with suspicion and contribute to the elaboration of statements that comprise justice done with their own hands as a form of contain the criminal act.